A calculation method of precise direct normal irradiance based on measured CSR. Issue 1 (January 2021) - Niu, Yisen; Wu, Zhaoxuan; Zhang, Kexin; Song, Jifeng
Abstract: Radiation from the circumsolar region called circumsolar radiation is part of direct solar radiation, but not all circumsolar radiation can be received by concentrating solar power (CSP). Circumsolar ratio (CSR) reflects the proportion of circumsolar normal irradiance in direct normal irradiance (DNI). CSR is related to the radial distribution of solar brightness (sunshape) and it is influenced by atmospheric turbidity and air mass (AM).Performance of CSP is affected by CSR, which should be considered in the CSP simulation and analysis. This work introduces a method of measuring CSR with a CCD camera and filters. Also a calculation method of DNI for different field of view based on the measured CSR is proposed.